Healthful heritage: A training on omega-3 fortified traditional noodles (“Mie Lethek”) in Caturharjo, Bantul, Yogyakarta - Suhendra; Salamah, Siti; Santosa, Imam (Universitas Ahmad Dahlan, 2025)
The Chemical Engineering Department of Universitas Ahmad Dahlan (UAD) conducted a Community Service Program (PKM) aimed at enhancing the quality of Mie Lethek, a traditional noodle dish, through omega-3 fortification. This initiative addressed the increasing demand for healthy food while preserving local culinary heritage. The program, conducted in Caturharjo, Bantul, involved 27 participants, including local vendors and members of the Family Welfare Empowerment (PKK) team. Activities included a presentation on omega-3 benefits, practical demonstrations of omega-3 fortification, and distribution of fortified noodle samples. Surveys revealed over 80% of participants gained new insights and expressed interest in adopting the innovation. Nutritional fortification improved product quality, particularly in increasing omega-3 content. This initiative highlights the potential for Mie Lethek to compete in the health food market and contribute to the local economy, demonstrating a scalable model for fortifying traditional foods with functional nutrients